(untitled) (Journal of Fiber Bioengineering and Informatics, 2016)
In this study, color emotion based on CNCS color system was investigated. The research included single color preference and multi-color coordination emotion. Six themes of International Textile color traded were selected as color samples. At the first step, forty-two single colors were regarded as color samples for color preference survey. At the second step, twenty-four kinds of color coordination were made according to six color concepts, and color emotion survey for multi-color coordination was conducted. In the second part, fifteen color emotion scales such as “modern-classic”, “formal-casual”, “gaudy-tasteful”, “lively-stiff”, “intellectual-nonintellectual”, “like-dislike” and so on were selected according to Semantic Differential Method. The survey was conducted among the undergraduate college students from Xi'an Polytechnic University. Color histogram was used to express the result of single color preference. It was clear that the popularity of these released colors was not average and the more favorite colors were pale chromatic colors. Factor Analysis and cluster analysis were used to conduct the data from the second part survey. Three factors were extracted and labeled “personality”, “taste”, and “fashion”. Twenty- four multi-color combinations were classified into three groups. It indicated that the comprehensive color emotion was more important than other factors.